2003
DOI: 10.1099/vir.0.18978-0
|View full text |Cite
|
Sign up to set email alerts
|

Orf virus-encoded interleukin-10 inhibits maturation, antigen presentation and migration of murine dendritic cells

Abstract: Orf virus (ORFV) belongs to the genus Parapoxvirus and induces cutaneous pustular lesions in sheep, goats and humans. ORFV is unusual in that it has the ability to reinfect its host and this suggests that the generation of immunological memory has been impaired, thus exposing the host to subsequent infection. The discovery that ORFV encodes an IL-10-like virokine raises the question of whether this factor adversely affects the cells that initiate the acquired immune response. We examined the effect of ORFV-IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Investigators have further suggested that ovIL-10 impairs generation of an acquired immune response and thus inhibits formation of immunologic memory needed for protection against subsequent exposures. 80 Viral IL-10 homologue studies have aided in understanding the mechanisms by which pathogens modulate the human immune response to favor infection or pathogen persistence, or both. Investigations into other diseases have revealed further mechanisms of immune modulation, and IL-10 in particular is thought to play a role.…”
Section: Other Viral Diseasesmentioning
confidence: 99%
“…Investigators have further suggested that ovIL-10 impairs generation of an acquired immune response and thus inhibits formation of immunologic memory needed for protection against subsequent exposures. 80 Viral IL-10 homologue studies have aided in understanding the mechanisms by which pathogens modulate the human immune response to favor infection or pathogen persistence, or both. Investigations into other diseases have revealed further mechanisms of immune modulation, and IL-10 in particular is thought to play a role.…”
Section: Other Viral Diseasesmentioning
confidence: 99%
“…Poxviruses modulate the immune response in infected hosts by inhibiting the synthesis and release of IL-1 from infected cells; encoding soluble cytokine receptors for tumor TNF-α, TNF-β, IL-1, and importantly, IFN-γ; synthesizing virus-encoded cytokines like epidermal growth factor and transforming growth factor, which antagonize the effects of host cytokines mediating the antiviral process [16,26]. In addition, inducing apoptosis in a significant number of antigen-presenting cells [20] as well as inducing IL-10 release that has the capacity to impair the initiation of an acquired immune response [16,21]. If the viruses fail to secrete such immunomodulating proteins, as when the respective genes are deleted or the viruses are inactivated, the strong immunogenicity of the viruses may induce host immune reactions which are no longer inhibited [19].…”
Section: Introductionmentioning
confidence: 99%
“…UV-treated VACV induces stronger costimulatory molecule expression on mouse BM-DCs than VACV itself, suggesting that active mechanisms inhibit the maturation process (71). In addition to the production of suppressive cytokines (e.g., IL-10) that are known to block DC maturation by orf virus (ORFV) (11,33), the mechanism used by poxviruses to inhibit DC maturation is still poorly understood. VACV also interferes with the maturation of immature human DCs, as indicated by the inhibition of the expression of many proteins known to be induced during the maturation process (20).…”
Section: Discussionmentioning
confidence: 99%